Segmentation by archetypes and psychotypes: a review of empirical evidence on impact on conversion and retention in B2C funnels - Rebets, Volodymyr (Global Prosperity, 2023)
Annotation. In recent years, marketers have increasingly discussed customer segmentation based on psychological archetypes and personality types. Software vendors claim that targeting “Heroes” or people with specific character traits performs better than traditional segmentation by age and income. However, when one starts looking for solid data, it turns out that most of the evidence consists of polished presentations without methodology or studies conducted on students filling out questionnaires. We analyzed 23 sources published between 2018 and 2022 in which at least some elements could be verified: sample sizes, control groups, and actual conversion figures. The results show that archetype-based messaging does indeed increase conversion rates by 12-34%, but only for certain product categories-those related to self-perception (such as sportswear and educational courses)-and only at specific stages of the sales funnel. Segmentation based on Big Five personality traits was largely ineffective across studies. At the same time, the real issues are rarely discussed: algorithms misclassify users in 35-45% of cases, content production costs increase by about 40%, and proper testing requires traffic volumes that most companies simply do not have. In short, psychological segmentation can work, but only selectively, at a high cost, and this reality is rarely communicated honestly.